Characterization of an insect cell-derived Theileria parva sporozoite vaccine antigen and immunogenicity in cattle - Nene, Vishvanath M.; Inumaru, S.; McKeever, Declan J.; Morzaria, S.P.; Shaw, M.; Musoke, A.J. (American Society for Microbiology, 1995)
Previous data showed that six out of a group of nine cattle inoculated with NS1-p67, a recombinant form of a 67-KDa Theileria parva sporozoite surface protein, were immune to East Coast fever. This bacterialy expressed antigen encoded all 709 amino acid residues of p67 fused to the C-terminal end of 87 residues derived from NS1, a structural protein of influenza virus, and a linker DNA sequence. NS1-p67 lacked reactivity with TpM 12, a monoclonal antibody to native p67, and had an estimated molecular mass of 110 KDa, as opposed to the calculated mass of 85,000 Da. We have used the baculovirus expression system in an attempt to express this parasite protein in a native form and thereby increase the protective capacity of the antigen. However, spodoptera frugiperda SF21AE cells infected with recombinant virus expressed p67 as a 100-KDa molecule. The host cells exhibited a limited capacity to glycosyylate this molecule to a 110-KDa form, and p67 was not exported to the surface membrane. TpM 12 did not bind to these recombinant forms but, at time points late during viral infection, reacted with a molecule of about 70 KDa. Since the bulk of insect cell-derived p67 was not expressed in an appropriate form, we tested the immunogenicity of these partially processed recombinant p67 forms in cattle. Two groups of three cattle were inoculated with antigen formulated either with saponin or Freund's adjuvant. As seen previously with NS1-p67, all animals developed high levels of anti-p67 antibodies that neutralized sporozoite infectivity in vitro, but antigen-specific T-cell proliferative responses were not detected in peripheral blood. Given the caveat of the small number of cattle analyzed, insect cell-derived p67 does not appear to be superior to NS1-67 as an immunogen, and the latter remains the molecule of choice for the development of vaccines against East Coast fever.